2012
DOI: 10.1142/s0219686712500059
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Optimal Sequence of Machining Operations in Setup Planning by Genetic Algorithms

Abstract: This paper aims at automatic generation of optimal sequence of machining operations in setup planning by Genetic Algorithm (GA) based on minimizing the number of setup changes and tool changes, subject to various machining precedence constraints. The GA has been reconstructed as the method of representing an operation is not as simple as assigning it a binary digit as in case of a chromosome in traditional GA but it has to be a distinct real number. Accordingly, the GA operators had to be modified. At the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Matlab 2016b was used for simulation of both heuristics and their comparison. Crossover and mutation rate are stochastic parameters for GA. For the present case, crossover and mutation rate was selected to be 0.9 and 0.1 respectively which has been recommended in literature [3,52]. While comparing the process plans obtained with GA, it was observed that process plans obtained by Kumar & Deb [53] were unable to maintain precedence constraints which resulted in infeasible plans.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Matlab 2016b was used for simulation of both heuristics and their comparison. Crossover and mutation rate are stochastic parameters for GA. For the present case, crossover and mutation rate was selected to be 0.9 and 0.1 respectively which has been recommended in literature [3,52]. While comparing the process plans obtained with GA, it was observed that process plans obtained by Kumar & Deb [53] were unable to maintain precedence constraints which resulted in infeasible plans.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Reduction in product cost and responsiveness can be observed by customizing the machining capabilities at product design stage and then the reuse of these capabilities at reconfiguration stage. Kumar and Deb [17] carried out an analysis by minimizing weighted function in case of a simultaneous set up and tool change. The results not only gave the optimal solution for each parameter but also optimized the overall effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Choice of constraints again depends on the problem and the availability of machining data. For example, Qiao et al (2000) used various process planning rules including precedence rules, clustering rules, adjacent order rules, and so on; Kumar and Deb (2012) have attempted to optimise operation sequences in set-up planning based on minimising the number of set-up changes and tool changes, subject to various machining precedence constraints. GAs have also been used for solving optimisation problems in production planning and control such as process route optimisation (Bo et al, 2006), multi-objective scheduling (Azadeh et al, 2010) and facility layout planning (Kundu and Dan, 2012).…”
Section: Review Of Previous Researchmentioning
confidence: 99%
“…One of the major challenges for optimisation here lies in minimising the overall manufacturing cost. Several researchers have approached the problem of minimising the cost by minimising changes in parameters like machine changes, tool changes, and set-up changes (Ma et al, 2000;Krishna and Rao, 2006;Kumar and Deb, 2012). We have adopted a similar approach by assuming that, in a particular industry and while operating a particular machine, the manufacturing cost increases with increase in the machining time for a part, provided other factors like machine set-up time, number of operators, etc., are held constant.…”
Section: Introductionmentioning
confidence: 99%